Medication preventing postictal hypoperfusion and cognitive side-effects in electroconvulsive therapy: A retrospective cohort study - Verdijk, Joey P. A. J.; Schuur, Gijsbert; Pottkämper, Julia C. M.; ten Doesschate, Freek; Hofmeijer, Jeannette; van Waarde, Jeroen A. (Frontiers in Psychiatry, 2023)
Background Electroconvulsive therapy (ECT) is associated with postictal confusion and cognitive side-effects. In rats, acetaminophen, non-steroidal anti-inflammatory drugs (NSAIDs) and calcium antagonists decreased postictal cerebral hypoperfusion along with reduction in postictal symptoms. In this study in ECT-patients, we explore associations between use of these potentially protective medications and occurrence of postictal confusion and cognitive outcome. Materials and Methods In this retrospective, naturalistic cohort study, patient-, treatment-, and ECT-characteristics, as well as occurrence of severe postictal confusion directly after ECT-sessions, were collected from medical files of 295 ECT-patients. Pre- and post-ECT-course measures of cognitive functioning were available in 109 major depressed patients. We used univariate and multivariate analyses to associate patient-, treatment-, and ECT-characteristics with severe postictal confusion and cognitive outcome. Results Use of potentially protective medications was not associated with reduced occurrence of severe postictal confusion. Censored multivariate analysis showed that use of calcium antagonists was associated with higher post-ECT cognitive scores (i.e., better cognitive outcome; β=2.23; p=0.047), adjusted for age (β=-0.02; p=0.23), sex (β=-0.21; p=0.73), pre-ECT cognitive score (β=0.47; p<0.0001) and post-ECT depression score (β=-0.02; p=0.62). Use of acetaminophen (β=-1.55; p=0.07) as well as NSAIDs (β=-1.02; p=0.23) showed no associations with post-ECT cognitive scores. Conclusion This study does not find arguments for protective effects of acetaminophen, NSAIDs or calcium antagonists against severe postictal confusion. As a preliminary finding, the use of calcium antagonists was associated with better cognitive outcome after ECT in our cohort. Prospective controlled studies are necessary.